The Insight into the Sex Differences in the Patients Diagnosed with Acute Coronary Syndromes Undergoing Percutaneous Coronary Intervention - Huma Naeem Tareen, Akhtar Sher, Fouzia Goher, Iftikhar Hussain, Mohsin Saif, Muhammad Rehan Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The limited knowledge is present about the outcomes associated with the patients diagnosed with acute coronary syndrome (ACS). The insufficient data about the sex difference in the post-interventions outcomes and disparities in management is available. Objective: This study aim was to determine the sex-related differences in the patient diagnosed with ACS. This study also aimed to determine how these differences have perished in a time span of one year. Study design: It is a retrospective study with the statistical approaches. Material and Methods: The data of the 1000 patients that visited to AFIC Rawalpindi was collected. The duration of the study was 6 months, from August 2021 to January 2022. The patients were diagnosed with the non-ST-segment elevation acute coronary syndrome were selected. The ethical and review board committee of the hospital approved the study. The patients were further grouped to ACS I and ACS II. Results: Out of the 1000 patients taken, there were 650 patients that had acute coronary syndrome I while there were 350 patients that had acute coronary syndrome II. Among the 650 patients of ACSI there were 430 males and 220 were female patients. And among the 350 ACSII there were 230 males and 120 were female. The study indicate that the older women have the higher cases with reported history of heart failure and hypertension. The higher mortality cases were also observed in the females. The association between coronary angiography in-hospital use and female gender was very weak. The physicians underestimate the risk associated with the diagnosed patients that leads to less use of invasive strategies for treatment of the men and women. Conclusion: Due to underestimation of the risks associated with the ACS patients the conservative methods are used for the treatment of the women. The poor in-hospital outcome are associated with the female gender. It was found that women are less likely to undergo coronary artery angioplasty and other cardiac procedures as compared to the male patients. Awareness is needed for both male and female to eliminate this gender disparity. Keywords: Coronary angiography, acute coronary syndrome, percutaneous coronary intervention, post-interventions outcomes and heart failure.